THE RELATIONSHIP BETWEEN SELF-CONCEPT AND PARENTAL SUPPORT WITH CAREER MATURITY OF STUDENTS OF JAKARTA 20 VOCATIONAL HIGH SCHOOL - Fitrianingsih, Hani; Karyaningsih, RR Ponco Dewi; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This research aims to find out the relationship between Self-Concept and Parental Support with Career Maturity in Students of Jakarta 20 Vocational High School. This study was conducted for seven months from February to September 2021. The research method used is the survey method. The sample used in this study was obtained by 146 respondents from students of the 12th grade of Jakarta 20 Vocational High School. Data collection is done through the dissemination of questionnaires using the likert scale. Based on research conducted there is a positive relationship between self-concept and career maturity and there is a positive relationship betweenparental support and career maturity.